Contrast-enhanced filter glass as well as preparation method and application thereof

By using the contrast-enhanced filter glass prepared with specific compositions and preparation methods, the problems of light string and light leakage in the optical fiber image transmission element are solved, efficient light absorption and filtering effect are achieved, and imaging contrast and clarity are improved.

CN119661074APending Publication Date: 2025-03-21CHINA BUILDING MATERIALS ACADEMY CO LTD

Patent Information

Application Number
CN202411771820.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The light-chain and light leakage problems between optical fibers in existing optical fiber image transmission components lead to low contrast and clarity, and the light absorption efficiency of traditional light-absorbing material glass cannot meet the needs of high definition and high contrast.

Method used

A composition of contrast-enhanced filter glass is adopted, including components such as SiO2, B2O3, Al2O3, etc., and the light absorption performance and filtering effect of the glass are improved through specific ratios and preparation methods.

Benefits of technology

It realizes low transmittance and strong light absorption capability in the wavelength range of 380-760nm, improves the imaging contrast and clarity of fiber image transmission elements, and is suitable for high resolution and high contrast fiber image transmission elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661074A_ABST
    Figure CN119661074A_ABST
Patent Text Reader

Abstract

The invention relates to contrast-enhanced filter glass as well as a preparation method and application thereof. The contrast-enhanced filter glass is prepared from the following components in percentage by mole: 64 to 78 percent of SiO2, 3 to 16 percent of B2O3, 5 percent of Al2O3, 0 to 1 percent of Li2O, 0 to 6 percent of Na2O, 0 to 12 percent of K2O, 0 to 1.5 percent of MgO, 0 to 2.5 percent of CaO, 0 to 1 percent of BaO, 0 to 1 percent of SrO, 0 to 1 percent of ZnO, 1 percent of TiO2, 1 percent of ZrO, 1 percent of CeO, 0 to 6 percent of Fe2O3, 0.1 to 1 percent of NiO, 1 percent of V2O, 2 percent of Co2O3, 0.2 percent of MoO, 0.1 to 2.5 percent of MnO2, 0.1 to 2 percent of Cr2O3, 1 percent of Nd2O3, 0.1 to 2 percent of The contrast-enhanced filter glass provided by the invention has good light absorption performance and filtering performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of glass material manufacturing, and in particular to a contrast-enhanced filter glass and a preparation method and application thereof. Background Art

[0002] Contrast-enhanced filter glass allows only specific wavelengths of light in the display device to pass through, while filtering out other irrelevant wavelengths of light, so that the display device can achieve a higher contrast. The optical properties of contrast-enhanced filter glass include high transmittance in the band that needs to be transmitted and extremely low transmittance in the band that needs to be cut off, which can achieve ultra-clear and true color on full-color displays. In addition, full-color displays can also reproduce colors more naturally.

[0003] Fiber optic image transmission elements include optical fiber panels, fiber optic image inverters, fiber optic light cones, etc. The image transmission mechanism of fiber optic image transmission elements is realized by utilizing the total reflection principle of optical fibers. The optical fibers constituting the fiber optic image transmission elements are prepared by hot melting and pressing of a low-refractive-index skin glass tube, a high-refractive-index core glass rod, and a light-absorbing glass fiber using a rod-tube combination and a vacuum drawing process. Since the optical fibers are completely tightly fused together by the skin glass, the adjacent optical fibers are close to each other, resulting in cross-talk between adjacent optical fibers. For example, due to the uneven temperature field or uneven drawing force during the preparation process, the uneven thickness of the skin glass tube may result, which may cause the input light to penetrate the skin during the total reflection process, resulting in light penetration and light leakage. Alternatively, the total reflection conditions of light are destroyed due to defects or contaminants at the contact interface of the optical fiber glass or the skin glass, causing light to be scattered. These scattered lights enter adjacent optical fibers and also cause cross-talk, which is an important factor directly affecting the imaging quality of the fiber optic image transmission element, such as contrast and clarity.

[0004] In order to solve the problems of light crosstalk and light leakage between optical fibers in optical fiber image transmission elements, it is usually adopted to fill the gaps between adjacent optical fibers with light-absorbing glass fibers to absorb stray light and reduce light crosstalk. The method of inserting light-absorbing glass fibers can effectively eliminate stray light. The light-absorbing glass is drawn into absorption fibers and inserted into the gaps between the arranged optical fibers to absorb light crosstalk and light leakage. However, it cannot completely achieve optical insulation. The key lies in the transmittance of the light-absorbing glass. The function of the light-absorbing glass is to absorb the stray light that penetrates the cortex of the optical fiber to achieve optical insulation and improve the contrast of the image. Light-absorbing glass is an important type of optical glass, which mainly achieves the absorption effect of interfering stray light and improves the clarity, contrast and other performance of optical components. However, with the expansion of application areas, the requirements for ultra-thin, lightweight, high-definition, and high-contrast fiber optic imaging components have become increasingly higher in recent years. Therefore, the light-absorbing glass is also required to have a better light absorption effect and absorb stray light more thoroughly. It must also cover the ultraviolet, visible to near-infrared bands and achieve the requirement of extremely low transmittance in the band that needs to be cut off.

[0005] Due to the inherent concentration difference between the light-absorbing glass and the low-refractive-index skin glass in the optical fiber image transmission element, different degrees of ion diffusion and mutual penetration are inevitable during the thermal processing. In addition, since the optical fiber image inverter in the optical fiber image transmission element also adds a thermal twisting process, the ion diffusion and mutual penetration of the two components at the contact interface between the glass material and the skin material are more serious than those of the optical fiber panel, resulting in a certain degree of decrease in the transmission characteristics of the optical fiber image inverter such as transmittance and contrast.

[0006] Ordinary light-absorbing glass still has a high transmittance in the visible light range at a thickness of 0.5 mm. As the thickness decreases, the transmittance will gradually increase. However, the light-absorbing materials of traditional optical fiber image transmission components generally have problems such as low stray light absorption efficiency and poor imaging contrast. This is because most of the light-absorbing materials are Fe 2 O 3 As a light absorbing colorant, although Fe 3+ Ions have good light absorption properties, but they are mainly concentrated in the infrared region. Their light absorption properties are poor in the visible light region. 3+ When Fe ions act as light absorbers, 3+It is difficult for ions to remain in an oxidized state in glass, especially for optical fiber wires with a diameter of less than 6μm. The coloring of ferric oxide will be unstable or even fade during the high-temperature drawing process. What is more serious is that the colored ions will diffuse into the skin glass of the optical fiber, which will weaken or eliminate the total reflection mechanism of the optical fiber, and will "poison" the photocathode material, which will have a serious impact on improving the image quality of the optical fiber image transmission element. A reducing atmosphere is also required to obtain a good light absorption effect. In addition, due to the Fe 3+ The ions are variable valence element ions, which are prone to changes in ion valence at high temperatures, thus directly affecting the light absorption effect. In particular, the light-absorbing glass used in optical fiber imaging components cannot meet the application requirements of high-definition and high-contrast optical fiber imaging components. Summary of the invention

[0007] The present invention aims at solving the above-mentioned problems in the prior art and provides a contrast-enhanced filter glass with good light absorption performance.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is:

[0009] A composition for contrast enhancement filter glass, comprising the following components in molar percentage: SiO 2 64-78%, B 2 O 3 3-16%, Al 2 O 3 0-5%, Li 2 O 0-1%, Na 2 O 0-6%, K 2 O 0-12%, MgO 0-1.5%, CaO 0-2.5%, BaO 0-1%, SrO 0-1%, ZnO 0-1%, TiO 2 0-1%, ZrO 2 0-1%, CeO 2 0-1%,Fe 2 O 3 0-6%, NiO 0.1-1%, V 2 O 5 0-1%,Co 2 O 3 0-2%, MoO 3 0-0.2%, MnO 2 0.1-2.5%, Cr 2 O 3 0.1-2%, Nd 2 O 3 0-1%, CuO 0.1-2%, F 2 0-1%.

[0010] The present invention also provides a preferred technical solution, a composition of a contrast-enhanced filter glass, preferably comprising the following components in molar percentage: SiO 2 68-76%, B 2 O 3 3-10%, Al 2 O 3 3-5%, Li 2 O 0-1%, Na 2 O 2-6%, K 2 O 3-9%, MgO 0.2-1.0%, CaO 1-2.5%, BaO 0-0.1%, SrO 0-0.2%, ZnO 0-0.1%, TiO 2 0-0.3%, ZrO 2 0-0.3%, CeO 2 0-0.1%,Fe 2 O 3 0.1-6%, NiO 0.3-1%, V 2 O 5 0-1%,Co 2 O 3 0.1-1.5%, MoO 3 0-0.2%, MnO 2 0.1-2.0%, Cr 2 O 3 0.1-1%, Nd 2 O 3 0-0.5%, CuO 0.1-1%, F 2 0.1-1%.

[0011] The present invention also provides a more preferred technical solution, a composition of a contrast enhancement type filter glass, comprising the following components in molar percentage: SiO 2 73%, B 2 O 3 4%,Al 2 O 3 4.8%, Na 2 O5.2%, K 2 O 7%, MgO 0.5%, CaO 1.5%, SrO 0.1%, Fe 2 O 3 0.4%, NiO 0.4%, Co 2 O 3 1.0%, MnO 2 0.3%,Cr 2 O 30.5%, CuO 0.8%, F 2 0.5%.

[0012] The present invention further provides a method for preparing contrast-enhanced filter glass using the composition, comprising the following steps:

[0013] (1) Raw material preparation: mixing the raw materials in proportion to obtain a raw material mixture;

[0014] (2) Glass melting: The raw material mixture is added into a crucible and melted at a first preset temperature. After the raw material mixture is melted, it is stirred until a clear and homogenous glass liquid is formed. Then, the raw material mixture is discharged at a second preset temperature and cast into a desired glass in a mold. After the glass is cooled and solidified, it is annealed to obtain a contrast-enhanced filter glass.

[0015] The first preset temperature is 1420-1520°C, the melting time is 5-8 hours, and the second preset temperature is 1360-1380°C.

[0016] The stirring is performed 2-3 times, the rotation speed of each stirring is 50-80 rpm, and the stirring time is 1-2 hours.

[0017] The annealing temperature is 550-600° C., and the annealing time is 24-36 hours.

[0018] The present invention further provides a contrast enhancement type filter glass, which is prepared according to the method.

[0019] The contrast-enhanced filter glass of the present invention is suitable for being used as a light-absorbing glass material for glass fibers when preparing optical fiber image transmission elements. Optical fiber image transmission elements include optical fiber panels, optical fiber image invertors, optical fiber light cones, optical fiber image transmission bundles, etc. The contrast-enhanced filter glass has a spectral transmittance of ≤2.5% within a wavelength range of 380-760nm at a thickness of 0.30±0.01mm and a thermal expansion coefficient of (80±5)×10 -7 / ℃; no crystallization occurs when kept at 850℃ for 6 hours.

[0020] The present invention further provides an application of contrast-enhanced filter glass as light-absorbing material glass on an optical fiber imaging element.

[0021] In the contrast enhancement filter glass of the present invention, SiO 2 It is the main component of the glass skeleton and plays a major role in the glass skeleton. It is also a component that improves chemical resistance. 2 The molar percentage (mol.%) of SiO is 64-78, preferably 68-76. 2When the content is lower than 64.0 mol%, it is difficult to obtain a thermal expansion coefficient similar to that of leather glass, and the chemical resistance of the glass will be reduced. 2 When the content is higher than 78.0 mol%, the high temperature viscosity of the glass will increase, causing the glass melting temperature to be too high.

[0022] B 2 O 3 It is an oxide that forms glass and is also a component of the glass skeleton. It is also a flux that reduces the viscosity of molten glass. 3 ] and boron-oxygen tetrahedron [BO 4 ] as the structural component, under different conditions, boron may exist in the form of triangular [BO 3 ] or boron-oxygen tetrahedron [BO 4 ] exists. Under high temperature melting conditions, it is generally difficult to form boron-oxygen tetrahedrons, and can only exist in the form of trihedrons. However, at low temperatures, under certain conditions, B 3+ It has a tendency to capture free oxygen to form tetrahedrons, making the structure compact and increasing the low-temperature viscosity of the glass. However, due to its characteristics of reducing the viscosity of glass at high temperatures and increasing the viscosity of glass at low temperatures, it is also the main component that reduces the refractive index of glass, which determines that its content range is relatively small. 2 O 3 The molar percentage (mol.%) is 3-16, preferably 3-10. 2 O 3 If the content of B is lower than 3 mol%, it cannot play a dissolving role and will reduce the chemical stability of the glass. 2 O 3 When the content of is greater than 16.0 mol%, the phase separation tendency of the glass will increase.

[0023] Al 2 O 3 An intermediate oxide of glass, Al 3+ There are two coordination states, namely, in tetrahedron or octahedron. When there is enough oxygen in the glass, aluminum oxygen tetrahedron [AlO 4 ], forming a continuous network with silicon-oxygen tetrahedrons. When there is insufficient oxygen in the glass, aluminum-oxygen octahedrons [AlO 6 ], which is a network outsider and is in the holes of the silicon-oxygen structure network, so it can react with SiO 2 It is the main body of glass network formation. 2 O 3 The molar percentage (mol.%) of Al is 0-5, preferably 3-5. 2 O 3 A content greater than 5.0 mol% will significantly increase the high-temperature viscosity of the glass, increase the melting temperature of the glass, and reduce the crystallization performance of the glass.

[0024] Li 2 O is an oxide outside the glass structure network, which mainly plays a role in reducing the viscosity of the glass melt. 2 The molar percentage (mol.%) of O is 0-1, Li 2 When the content of O is greater than 1 mol%, the thermal expansion coefficient of the glass will increase.

[0025] Na 2 O is an oxide outside the glass structure network, Na 2 The molar percentage (mol.%) of O is 0-6, preferably 2-6. 2 When the content of O is greater than 6 mol%, the thermal expansion coefficient of the glass will increase and the crystallization tendency of the glass will increase.

[0026] K 2 O is an oxide outside the glass structure network, K 2 The molar percentage (mol.%) of O is 0-12, preferably 3-9. 2 When the content of O is greater than 12 mol%, the thermal expansion coefficient of the glass will increase and the crystallization tendency of the glass will increase.

[0027] MgO is an oxide outside the glass structure network and is used to adjust the crystallization temperature of the glass. The molar percentage (mol.%) of MgO is 0-1.5, preferably 0.2-1. When the content of MgO is greater than 1.5 mol.%, the thermal expansion coefficient and crystallization tendency of the glass will increase.

[0028] CaO is an oxide outside the glass structure network, and the molar percentage (mol.%) of CaO is 0-2.5, preferably 1-2.5. If the content of CaO is greater than 2.5 mol.%, the chemical resistance of the glass will be reduced.

[0029] BaO is an oxide outside the glass structure network and is used to adjust the crystallization temperature of the glass. The molar percentage (mol.%) of BaO is 0-1, preferably 0-0.1. If the content of BaO is greater than 1 mol.%, the chemical resistance of the glass will be reduced.

[0030] SrO is an oxide outside the glass structure network and is used to adjust the crystallization temperature of the glass. The molar percentage (mol.%) of SrO is 0-1, preferably 0-0.2. If the content of SrO is greater than 1 mol.%, the chemical resistance of the glass will be reduced.

[0031] ZnO is used to adjust the crystallization temperature of the glass. The molar percentage (mol.%) of ZnO is 0-1, preferably 0-0.1. If the content of ZnO is greater than 1 mol.%, the chemical resistance of the glass will be reduced.

[0032] TiO 2 It is used to adjust the chemical stability and crystallization of glass. 2 The molar percentage (mol.%) of TiO is 0-1, preferably 0-0.3. 2 The content of greater than 1.0 mol% will reduce the chemical resistance of the glass and increase the tendency of crystallization.

[0033] ZrO 2 It is used to adjust the crystallization temperature of glass. Appropriate ZrO 2 It is beneficial to clarify the glass liquid and eliminate streaks during the glass melting process. ZrO 2 The molar percentage (wt.%) of ZrO is 0-1, preferably 0-0.3. 2 The content of is greater than 1 mol%, which will increase the melting and molding temperature of the glass.

[0034] CeO 2 It is a rare earth oxide that mainly regulates the crystallization properties of glass and acts as a glass clarifier. CeO 2 The molar percentage (mol.%) is 0-1, preferably 0-0.1, CeO 2 When the content is greater than 1 mol%, the crystallization tendency of the glass will increase.

[0035] Fe 2 O 3 It is a light absorbing colorant in filter glass. 2 O 3 The molar percentage (mol.%) of Fe is 0-6, preferably 0.1-6. 3+ Ions have excellent light absorption and filtering properties, and the absorption range is mainly concentrated in the visible light to infrared region. 2 O 3 When the content is greater than 6 mol%, the chemical stability of the glass will be reduced and the crystallization tendency of the glass will be increased.

[0036] NiO is a light absorbing colorant for filter glass, and the molar percentage (mol.%) of NiO is 0.1-1, preferably 0.3-1. 2+ It has good absorption effect in the visible light region. When the NiO content is greater than 1 mol%, it will reduce the chemical stability of the glass and increase the crystallization tendency of the glass.

[0037] V 2 O 5 It is a light absorbing colorant for filter glass, V 2 O 5 The molar percentage (mol.%) is 0-1, V 2 O 5It can play the role of solidification and coloring, thus making the light absorption coloring and filtering performance more stable. 2 O 5 When the content is greater than 1 mol%, the chemical stability of the glass will be reduced and the crystallization tendency of the glass will be increased.

[0038] Co 2 O 3 It is a light absorbing colorant for filter glass, Co 2 O 3 The molar percentage (mol.%) of Co is 0-2, preferably 0.1-1.5. 2 O 3 It can combine with other coloring ions to form a stable form in the glass, thus making the light absorption, coloring and filtering properties more stable. 2 O 3 When the content is greater than 2 mol%, the chemical stability of the glass will be reduced and the crystallization tendency of the glass will be increased.

[0039] MoO 3 It is a transition metal oxide and a light-absorbing colorant for filter glass. MoO 3 The molar percentage (mol.%) is 0-0.2, MoO 3 It can combine with iron ions, cobalt ions, etc. to form stable coloring in glass. By using the composite absorption effect, it can ensure the absorption of stray light in the visible light wavelength range, obtain better light absorption effect, and make the light absorption curve have no obvious transmission peak in the visible light region. However, MoO 3 When the content is greater than 0.2 mol%, the chemical stability of the glass will be reduced and the crystallization tendency of the glass will be increased.

[0040] MnO 2 It is a light absorbing colorant for filter glass, and Mn 4+ It has stable light absorption and filtering properties in the visible light wavelength range and can form stable coloring in glass. 2 The molar percentage (mol.%) of MnO is 0.1-2.5, preferably 0.1-2. 2 When the content is greater than 2.5 mol%, the chemical stability of the glass will be reduced and the crystallization tendency of the glass will be increased.

[0041] Cr 2 O 3 It is a light absorbing colorant for filter glass, Cr 2 O 3 The molar percentage (mol.%) of Cr is 0.1-2, preferably 0.1-1. 2 O 3 If the content is greater than 2 mol%, the chemical resistance of the glass will be reduced and the tendency of crystallization will be increased.

[0042] Nd 2 O 3 It is a light absorbing colorant for filter glass, rare earth ion Nd 3+ The spectral characteristics, light absorption capacity and light filtering performance in glass are very stable, and Nd 3+ There are strong absorption peaks at 548nm, 568nm, and 588nm. A small amount of Nd 3 + It can play a composite absorption role in glass. 2 O 3 The molar percentage (mol.%) of Nd is 0-1, preferably 0-0.5. 2 O 3 When the content is greater than 1 mol%, the chemical stability of the glass will be reduced and the crystallization tendency of the glass will be increased.

[0043] CuO is a light absorbing colorant in filter glass. 2+ 、Co 3+ , Mn 2+ The combination of CuO and CuO forms a stable coloring in the glass. The composite absorption effect can ensure the absorption of stray light in the visible light wavelength range, obtain better light absorption and filtering effects, and make the light absorption curve have no obvious transmission peak in the visible light region. The molar percentage (mol.%) of CuO is 0.1-2, preferably 0.1-1. However, when the content of CuO is greater than 2 mol.%, the crystallization tendency of the glass will be increased.

[0044] F 2 It is used to adjust the melting temperature and crystallization temperature of glass. 2 The molar percentage of F is 0-1 mol.%, preferably 0.1-1. 2 When the content is greater than 1 mol%, the chemical resistance of the glass will be reduced.

[0045] Compared with the prior art, the contrast-enhanced filter glass of the present invention has the following beneficial effects:

[0046] (1) The preparation method of the contrast-enhanced filter glass of the present invention is simple and low-cost, and can effectively improve the filter performance of the glass;

[0047] (2) The present invention has good light absorption and filtering properties, with a spectral transmittance of ≤2.5% in the wavelength range of 380-760nm at a thickness of 0.3±0.01mm, and has strong and uniform light absorption and filtering effects;

[0048] (3) The present invention has a thermal expansion coefficient and viscosity characteristics similar to those of the skin glass in the optical fiber imaging element. The thermal performance meets the requirements of the optical fiber imaging element preparation process. The thermal expansion coefficient at 30-300°C is (80±5)×10 -7 / ℃;

[0049] (4) The contrast-enhanced filter glass prepared by the present invention has the advantages of no stones or bubbles inside the glass after melting, no crystallization occurs when kept at 850° C. for 6 hours, good anti-crystallization performance, and good chemical resistance stability;

[0050] (5) The contrast-enhanced filter glass of the present invention is applied to optical fiber imaging elements as light-absorbing glass, and can effectively improve the imaging contrast and clarity of the optical fiber imaging elements.

[0051] The contrast-enhanced filter glass of the present invention has the advantages of excellent filtering performance in the wavelength range of 380nm-760nm and extremely low transmittance. The present invention is based on the existing light-absorbing material glass, improves the light absorption effect and filtering performance of the light-absorbing material glass by improving the colorant composition ratio, reduces the ion diffusion and mutual penetration between the two components of the light-absorbing material glass and the skin glass, optimizes the preparation technology, and uses the contrast-enhanced filter glass of the present invention as the light-absorbing material glass. It is applied in the optical fiber image transmission element, which can effectively improve the imaging contrast and clarity of the optical fiber image transmission element, especially for preparing the optical fiber image inverter. The prepared optical fiber image inverter has the advantages of high resolution, high contrast, high transmittance, and high uniformity, further improving the product performance.

[0052] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 This is a transmittance curve of the contrast enhancement type filter glass provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0054] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with preferred embodiments, but they are not intended to limit the present invention. In the following description, different "one embodiment" or "embodiment" do not necessarily refer to the same embodiment. In addition, specific features, structures, or characteristics in one or more embodiments may be combined in any suitable form.

[0055] Table 1 Chemical composition (mol.%) and properties of contrast enhancement filter glass examples

[0056]

[0057] See also Figure 1 , which is the transmittance curve of the contrast-enhanced filter glass. It can be seen that it has strong light absorption ability and filtering effect in the wavelength range of 380-760nm, and the spectral transmittance is less than 2.5%. It can be seen that the light absorption effect on visible light is very obvious.

[0058] Herein, all "mol. %" are based on the total molar amount of the final glass composition. The glass chemical compositions (mol. %) of the examples are listed in detail in Table 1.

[0059] The parameters, measuring methods and instruments for the contrast enhancement filter glass of the present invention are as follows:

[0060] (1) The transmittance of the filter glass is measured using a transmittance tester;

[0061] (2) Average linear thermal expansion coefficient α at 30-300℃ 30 / 300 [×10 -7 / ℃] is measured using a horizontal dilatometer and the method specified in GB / T 16920-2015.

[0062] Example 1

[0063] Select raw materials according to the glass composition of Example 1 in Table 1, so that the ingredients meet the glass chemical composition of Table 1, and then prepare the contrast enhancement filter glass according to the following steps:

[0064] (1) Raw material preparation: weigh raw materials of quartz sand, boric acid, aluminum oxide, sodium carbonate, potassium carbonate, basic magnesium carbonate, calcium carbonate, barium nitrate, strontium carbonate, zinc oxide, titanium dioxide, zirconium oxide, cerium oxide, iron trioxide, nickel oxide, vanadium pentoxide, molybdenum trioxide, manganese dioxide, potassium chromate and copper oxide according to a molar ratio, mix them evenly, and obtain a raw material mixture;

[0065] (2) Glass melting: The raw material mixture is added into a crucible and melted at 1420°C for 8 hours. After the raw material mixture is melted, it is stirred twice, each stirring speed is 50 rpm, each stirring time is 1 hour, and the interval time between the two stirrings is 30 minutes, until a clear and homogenous glass liquid is formed. Then, the material is discharged at 1380°C and cast into a mold to form the required glass. After the glass is cooled and solidified, it is annealed at 600°C for 24 hours to obtain a contrast-enhanced filter glass.

[0066] The glass sheet (thickness 0.30±0.01 mm) made from the raw materials of Example 1 was tested to have a spectral transmittance of <2.5% in the wavelength range of 380-760 nm and no crystallization after being kept at 850° C. for 6 hours.

[0067] Example 2

[0068] Select raw materials according to the glass composition of Example 2 in Table 1, so that the ingredients meet the glass chemical composition of Table 1, and then prepare the contrast enhancement filter glass according to the following steps:

[0069] (1) Raw material preparation: weigh raw materials of quartz sand, boric acid, aluminum oxide, lithium carbonate, sodium carbonate, potassium carbonate, basic magnesium carbonate, calcium carbonate, zirconium oxide, nickel oxide, cobalt trioxide, molybdenum trioxide, manganese dioxide, potassium chromate, copper oxide and calcium fluoride in a molar ratio, mix them evenly, and obtain a raw material mixture;

[0070] (2) Glass melting: The raw material mixture is added into a crucible and melted at 1520°C for 5 hours. After the raw material mixture is melted, it is stirred for 3 times, each stirring speed is 80 rpm, each stirring time is 1 hour, and the interval time between each stirring is 1 hour, until a clear and homogenous glass liquid is formed. Then, the material is discharged at 1360°C and cast into a mold to form the required glass. After the glass is cooled and solidified, it is annealed at 550°C for 36 hours to obtain a contrast-enhanced filter glass.

[0071] The glass sheet (thickness 0.30±0.01 mm) made from the raw materials of Example 2 was tested to have a spectral transmittance of <2.5% in the wavelength range of 380-760 nm and no crystallization after being kept at 850° C. for 6 hours.

[0072] Example 3

[0073] Select raw materials according to the glass composition of Example 3 in Table 1, so that the ingredients meet the glass chemical composition of Table 1, and then prepare the contrast enhancement filter glass according to the following steps:

[0074] (1) Raw material preparation: weigh raw materials of quartz sand, boric acid, aluminum oxide, sodium carbonate, potassium carbonate, basic magnesium carbonate, calcium carbonate, strontium carbonate, ferric oxide, nickel oxide, cobalt oxide, manganese dioxide, potassium chromate, copper oxide and calcium fluoride according to a molar ratio, mix them evenly, and obtain a raw material mixture;

[0075] (2) Glass melting: The raw material mixture is added into a crucible and melted at 1470°C for 7 hours. After the raw material mixture is melted, it is stirred twice, each stirring speed is 70 rpm, each stirring time is 2 hours, and the interval time between each stirring is 30 minutes, until a clear and homogenous glass liquid is formed. Then, the material is discharged at 1370°C and cast into a mold to form the required glass. After the glass is cooled and solidified, it is annealed at 580°C for 30 hours to obtain a contrast-enhanced filter glass.

[0076] The glass sheet (thickness 0.30±0.01 mm) made from the raw materials of Example 3 was tested to have a spectral transmittance of less than 2.5% in the wavelength range of 380-760 nm and no crystallization after being kept at 850° C. for 6 hours.

[0077] Example 4

[0078] Select raw materials according to the glass composition of Example 4 in Table 1, so that the ingredients meet the glass chemical composition of Table 1, and then prepare the contrast enhancement filter glass according to the following steps:

[0079] (1) Raw material preparation: weigh raw materials of quartz sand, boric acid, aluminum oxide, sodium carbonate, potassium carbonate, basic magnesium carbonate, calcium carbonate, barium nitrate, titanium dioxide, ferric oxide, nickel oxide, cobalt oxide, manganese dioxide, potassium chromate, neodymium oxide, copper oxide and calcium fluoride in a molar ratio, mix them evenly, and obtain a raw material mixture;

[0080] (2) Glass melting: The raw material mixture is added into a crucible and melted at 1450°C for 7 hours. After the raw material mixture is melted, it is stirred for 3 times. The speed of each stirring is 60 rpm. The stirring time is 1.5 hours. The interval time between each stirring is 40 minutes until a clear and homogenous glass liquid is formed. Then, the material is discharged at 1365°C and cast into a mold to form the required glass. After the glass is cooled and solidified, it is annealed at 570°C for 26 hours to obtain a contrast-enhanced filter glass.

[0081] The glass sheet (thickness 0.30±0.01 mm) made from the raw materials of Example 4 was tested to have a spectral transmittance of <2.5% in the wavelength range of 380-760 nm and no crystallization after being kept at 850° C. for 6 hours.

[0082] Example 5

[0083] Select raw materials according to the glass composition of Example 5 in Table 1, so that the ingredients meet the glass chemical composition of Table 1, and then prepare the contrast enhancement filter glass according to the following steps:

[0084] (1) Raw material preparation: weigh raw materials of quartz sand, boric acid, lithium carbonate, barium nitrate, strontium carbonate, zinc oxide, titanium dioxide, zirconium oxide, cerium oxide, ferric oxide, nickel oxide, vanadium pentoxide, cobalt oxide, molybdenum trioxide, manganese dioxide, potassium chromate, neodymium oxide and copper oxide according to a molar ratio, mix them evenly, and obtain a raw material mixture;

[0085] (2) Glass melting: The raw material mixture is added into a crucible and melted at 1490° C. for 8 hours. After the raw material mixture is melted, it is stirred for 3 times, each stirring speed is 70 rpm, each stirring time is 2 hours, and the interval time between each stirring is 30 minutes, until a clear and homogenous glass liquid is formed. Then, the material is discharged at 1370° C. and cast into a mold to form the required glass. After the glass is cooled and solidified, it is annealed at 590° C. for 28 hours to obtain a contrast-enhanced filter glass.

[0086] The glass sheet (thickness 0.30±0.01 mm) made from the raw materials of Example 5 was tested to have a spectral transmittance of less than 2.5% in the wavelength range of 380-760 nm and no crystallization after being kept at 850° C. for 6 hours.

[0087] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A composition for contrast-enhanced filter glass, characterized in that: The invention comprises the following components in mole percentage: SiO2 64-78%, B2O3 3-16%, Al2O3 0-5%, Li2O 0-1%, Na2O 0-6%, K2O 0-12%, MgO0-1.5%, CaO 0-2.5%, BaO 0-1%, SrO 0-1%, ZnO 0-1%, TiO20-1%, ZrO2 0-1%, CeO2 0-1%, Fe2O3 0-6%, NiO 0.1-1%, V2O5 0-1%, Co2O3 0-2%, MoO3 0-0.2%, MnO2 0.1-2.5%, Cr2O3 0.1-2%, Nd2O3 0-1%, CuO 0.1-2%, and F2 0-1%.

2. The contrast enhancement filter glass composition according to claim 1, characterized in that: The invention comprises the following components in mole percentage: SiO2 68-76%, B2O3 3-10%, Al2O3 3-5%, Li2O 0-1%, Na2O 2-6%, K2O 3-9%, MgO 0.2-1.0%, CaO 1-2.5%, BaO 0-0.1%, SrO 0-0.2%, ZnO 0-0.1%, TiO2 0-0.3%, ZrO2 0-0.3%, CeO2 0-0.1%, Fe2O3 0.1-6%, NiO 0.3-1%, V2O5 0-1%, Co2O3 0.1-1.5%, MoO3 0-0.2%, MnO2 0.1-2.0%, Cr2O3 0.1-1%, Nd2O3 0-0.5%, CuO 0.1-1%, F20.1-1%.

3. The contrast enhancement filter glass composition according to claim 2, characterized in that: It includes the following components in molar percentage: SiO2 73%, B2O3 4%, Al2O3 4.8%, Na2O 5.2%, K2O 7%, MgO 0.5%, CaO 1.5%, SrO 0.1%, Fe2O3 0.4%, NiO 0.4%, Co2O3 1.0%, MnO2 0.3%, Cr2O3 0.5%, CuO 0.8%, and F2 0.5%.

4. A method for preparing a contrast-enhanced filter glass using the composition according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Raw material preparation: mixing the raw materials in proportion to obtain a raw material mixture; (2) Glass melting: The raw material mixture is added into a crucible and melted at a first preset temperature. After the raw material mixture is melted, it is stirred until a clear and homogenous glass liquid is formed. Then, the raw material mixture is discharged at a second preset temperature and cast into a desired glass in a mold. After the glass is cooled and solidified, it is annealed to obtain a contrast-enhanced filter glass.

5. The method according to claim 4, characterized in that The first preset temperature is 1420-1520°C, the melting time is 5-8 hours, and the second preset temperature is 1360-1380°C.

6. The method according to claim 4, characterized in that The stirring is performed 2-3 times, the rotation speed of each stirring is 50-80 rpm, the stirring time of each stirring is 1-2 hours, and the stirring interval time is 30 minutes to 1 hour.

7. The method according to claim 4, characterized in that The annealing temperature is 550-600° C., and the annealing time is 24-36 hours.

8. A contrast-enhanced filter glass, characterized in that: Prepared according to the method according to any one of claims 4 to 7.

9. The contrast enhancement filter glass according to claim 8, characterized in that: The contrast-enhanced filter glass has a spectral transmittance of ≤2.5% in the wavelength range of 380-760 nm at a thickness of 0.30±0.01 mm; a thermal expansion coefficient of (80±5)×10 -7 / ℃; no crystallization occurs when kept at 850℃ for 6 hours.

10. Use of the contrast-enhanced filter glass according to claim 8 or 9 as light-absorbing material glass in an optical fiber imaging element.

Citation Information

Patent Citations

  • Low-refractive glass applied to drawing formation preparation of optical fiber faceplate and preparation method thereof

    CN106517772A

  • Visible light absorbing glass and preparation method and application thereof

    CN110040941A

  • Ultraviolet, visible and near-infrared light absorbing glass as well as preparation method and application thereof

    CN110156317A

  • Light absorption material glass for optical fiber image transmission element and preparation method thereof

    CN111410423A

  • Light absorption material glass for high-contrast optical fiber image inverter and preparation method of light absorption material glass

    CN115368014A

Cited By

  • High-thermal-stability cut-off glass as well as preparation method and application thereof

    CN120504492A

  • Light absorption glass for preparing liquid flash capillary tube array and preparation method and application of light absorption glass

    CN122167031A